Bone health and its association with vitamin D and other covariates: A community-based study among women in a rural area of West Bengal - Tania Pan; Aparajita Dasgupta; Bobby Paul; Lina Bandyopadhyay; Amal Titto V. Augustine; Sweta Suman (Indian Journal of Public Health, 2020)
Background: Low bone mineral density (BMD) is implicated in the pathogenesis of osteoporosis and osteopenia, and primarily manifest as fragile bones. This is a rapidly emerging global health problem with increasing prevalence in India. Objectives: The objective of this was to assess the status of bone health and find its determinants among women aged 40 years and above in a rural population of West Bengal. Methods: A community-based cross-sectional study was conducted from May 2017 to April 2018 among 260 women aged 40 years and above residing in the selected villages of Singur through multistage random sampling. Each respondent was interviewed using a structured schedule. Serum Vitamin D and calcium levels were investigated. BMD was assessed through calcaneal quantitative ultrasound. Osteoporosis was diagnosed among those with T-score ≤−2.5, while those with 25(OH) Vitamin D <30 ng/ml were classified to have Vitamin D insufficiency (VDI). Individuals with BMD T-score <−1 were considered to have low BMD. Inferential statistics were employed to find the associates of poor bone health. Results: Out of 260 participants, 34 (13.1%) were screened positive for osteoporosis and 77.7% had low BMD. Approximately 75% had VDI. On multivariable analysis, VDI (adjusted odds ratio [95% confidence interval] = 4.13 [2.12, 8.37]) was a significant predictor of low BMD after adjustment for poor education, decreasing diet score, menopause, presence of comorbidity, underweight, and overweight explaining 43.6% of the variance. Conclusion: Serum Vitamin D levels are implicated to play a crucial role in bone metabolism; however, its effect on the body in accordance with other important hormones should be explored.